α-Terpineol reactions with the nitrate radical: Rate constant and gas-phase products - Jones, Brian T.; Ham, Jason E. (Atmospheric environment (1994), 2008)
The bimolecular rate constant of k NO 3 + α-terpineol (16 ± 4) × 10 −12 cm 3 molecule −1 s −1 was measured using the relative rate technique for the reaction of the nitrate radical (NO 3 ) with α-terpineol (2-(4-methyl-1-cyclohex-3-enyl)propan-2-ol) at 297 ± 3 K and 1 atmosphere total pressure. To more clearly define part of α-terpineol's indoor environment degradation mechanism, the products of α-terpineol + NO 3 reaction were investigated. The identified reaction products were: acetone, glyoxal (HC( O)C( O)H), and methylglyoxal (CH 3C( O)C( O)H). The use of derivatizing agents O-(2,3,4,5,6-pentafluorobenzyl)hydroxylamine (PFBHA) and N, O-bis(trimethylsilyl) trifluoroacetamide (BSTFA) were used to propose the other major reaction products: 6-hydroxyhept-5-en-2-one, 4-(1-hydroxy-1-methylethyl)-1-methyl-2-oxocyclohexyl nitrate, 5-(1-hydroxy-1-methylethyl)-2-oxocyclohexyl nitrate, 1-formyl-5-hydroxy-4-(hydroxymethyl)-1,5-dimethylhexyl nitrate, and 1,4-diformyl-5-hydroxy-1,5-dimethylhexyl nitrate. The elucidation of these products was facilitated by mass spectrometry of the derivatized reaction products coupled with plausible α-terpineol + NO 3 reaction mechanisms based on previously published volatile organic compound + NO 3 gas-phase mechanisms. The additional gas-phase products (2,6,6-trimethyltetrahydro-2 H-pyran-2,5-dicarbaldehyde and 2,2-dimethylcyclohexane-1,4-dicarbaldehyde) are proposed to be the result of cyclization through a reaction intermediate.